Public Policy on Oral Health and Old Age: a Global View - David E. Barmes, BDSc, DDSc (Blackwell Synergy, 2000)
This paper reviews major trends in the global demography and oral health status of populations, the challenges faced in ensuring successful aging because of these trends, and basic principles to guide public policy responses. Virtually all populations in which the dental caries prevalence reached high levels in the first half of the 20th century have experienced large reductions. A feared increase of the disease in the developing world has been far less than expected. Some countries that did suffer large increases dating from the 1960s already have managed to return to their former low levels because of timely use of preventive measures. Improving oral hygiene and a consequent reduction in the Occurrence and severity of periodontal diseases further bolster the mainly positive trend in global oral health. Only in the former socialist economies is oral health status worsening. These positive changes have brought the expectation that an intact and well-functioning dentition should last for life, no matter how extended the lifespan becomes.